2008
DOI: 10.1165/rcmb.2007-0045oc
|View full text |Cite
|
Sign up to set email alerts
|

The Lung Responds to Zymosan in a Unique Manner Independent of Toll-Like Receptors, Complement, and Dectin-1

Abstract: In vitro studies indicate that the inflammatory response to zymosan, a fungal wall preparation, is dependent on Toll-like receptor (TLR) 2, and that this response is enhanced by the dectin-1 receptor. Complement may also play an important role in this inflammatory response. However, the relevance of these molecules within the in vivo pulmonary environment remains unknown. To examine pulmonary in vivo inflammatory responses of the lung to zymosan, zymosan was administered by intratracheal aerosolization to C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 84 publications
2
15
0
1
Order By: Relevance
“…As before, the inhibition of surfactant function with EDTA had no effect, even in the Dectin-1 deficient animals ( Figure 4A ). In contrast, and despite the convincing in vitro data (see Figure 1 ), we found that Dectin-1 was not essential for inflammatory responses to zymosan in vivo , even in the presence of EDTA ( Figure 4B ); a finding similar to that reported previously [22].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As before, the inhibition of surfactant function with EDTA had no effect, even in the Dectin-1 deficient animals ( Figure 4A ). In contrast, and despite the convincing in vitro data (see Figure 1 ), we found that Dectin-1 was not essential for inflammatory responses to zymosan in vivo , even in the presence of EDTA ( Figure 4B ); a finding similar to that reported previously [22].…”
Section: Resultssupporting
confidence: 85%
“…These data therefore suggest that there are other innate fungal recognition systems in the lung, which have yet to be defined, but may involve more recently identified receptors such as Dectin-2 [24] or Mincle [45]. A role for complement, TLR2, TLR4 and MyD88 has already been ruled out [22].…”
Section: Discussionmentioning
confidence: 88%
“…Intratracheal administration of zymosan has been shown to induce pulmonary inflammation in animal models [13]. It stimulates the oxidative burst in macrophages and neutrophils following internalization [14].…”
Section: Introductionmentioning
confidence: 99%
“…These advances are likely to replace techniques that rely on surgical incision of the trachea for instillation of fungal cells [see videos in (Helms et al, 2010; Reddy et al, 2012)]. Dispersion of fungal cells into the pulmonary parenchyma may be enhanced by brief mechanical ventilation (Hasenberg et al, 2011) or by use of a microsprayer attached to the syringe tip (Kelly et al, 2008). The detergent Tween-20 is commonly used to prepare fungal cell suspensions for intranasal and intratracheal delivery.…”
Section: General Aspects Of Vertebrate Fungal Infection Modelsmentioning
confidence: 99%